Fe y Trabajo: domestic service, catholic associations and gender in the nineteenth fifties - Vazquez Lorda, Lilia; Pérez, Inés (Centro Interdisciplinario de Investigaciones en Género. IdIHCS (CONICET - UNLP). Facultad de Humanidades y Ciencias de la Educación, Universidad Nacional de La Plata, 2019)
Fe y Trabajo, published between 1944 and 1962, was the publication of the Catholic Association of Female Domestic Workers. In its pages, discourses that built a model of a docile and submissive worker overlapped with others that promoted workers' unionization. In this article we situate this case in relation to other Catholic associations of employees, highlighting its peculiarities. We also analyze the newsletter transformations over the period in which it was published, considering the changes in the political context, and the place of the gendered representations in the discourses of vindication of workers' rights.